Lung cancer survival in China and world-wide: results from CONCORD-3 - Hongcheng Zhu; Veronica Di Carlo; Fatima Baloch; Claudia Allemani; Michel Coleman (The Lancet Regional Health. Western Pacific)
Background: In 2015, the CONCORD programme initiated global surveillance of trends in population-based cancer survival as an indicator of health system performance and to support the formulation of global cancer control policies. In 2018, the third cycle of the programme, CONCORD-3, extended the worldwide monitoring of cancer survival trends to include data up to 2014. CONCORD-3 analysed survival data for over 37 million adults (15-99 years) who were diagnosed with one of 18 common cancers between 2000 and 2014, including 6.1 million individuals diagnosed with lung cancer. Anonymised individual patient records were contributed by 290 population-based cancer registries in 61 countries, including 21 in China. Methods: Tumours were classified into three major groups based on ICD-O-3 morphology codes: small-cell lung cancer (SCLC), non-small cell lung cancer (NSCLC) (comprising adenocarcinoma, large cell carcinoma, and squamous cell carcinoma), and lung cancer not otherwise specified (NOS). Trends in 5-year net survival in each morphology group were estimated for patients diagnosed during 2000-2004, 2005-2009 and 2010-2014, using the non-parametric Pohar Perme estimator. Background mortality was adjusted using life tables of all-cause mortality rates by single year of age, sex, single calendar year and, where available, race/ethnicity, for each country or region. All-ages survival estimates were standardised using the International Cancer Survival Standard weights. Survival trends have also been compared between China, the Western Pacific region and other countries. Findings: The proportion of non-small cell lung cancers ranged from 36% in China to over 80% in Guadeloupe, Martinique and Taiwan. Small-cell lung cancers accounted for 13% overall, with an international range from 3% to 17%. Almost one-fifth (19%) of lung cancers tumours were assigned a non-specific morphology (NOS), with the proportion varying from 8% in Belgium to over 50% in China, India, and Thailand. For patients diagnosed during 2010-2014, age-standardised 5-year net survival for NSCLC was below 10% in Bulgaria, Chile and Guadeloupe, but reached 39% in Japan. Age-standardized 5-year net survival for SCLC was consistently below 15% in all countries. Between 2000-2004 and 2010-2014, 5-year survival changed very little in each morphology group and in most countries. However, 5-year survival for NSCLC improved by 10% or more in Korea (from 16% in 2000–2004 to 29% in 2010–2014) and Taiwan (from 13% to 23%). Interpretation: These findings provide a global overview of lung cancer survival trends by morphology, derived from population-based cancer registries. They can inform public health strategies aimed at reducing disparities in outcomes. Lung cancer survival varies widely between China and other Western-Pacific countries. Accurate pathological classification is critical for improved analysis of international inequalities in lung cancer survival. We encourage population-based cancer registries with high-quality data in China and other Western Pacific countries to join the global effort, including the ongoing CONCORD-4 study.